Evaluation ofchilli genotypes of tripura based on morpho-chemical traits (Bangladesh Journal of Botany, 2026)
This study evaluated 15 local chilli genotypes (TCG1-15) for morphological traits, yield attributes, and biochemical properties during the rabi seasons of 2019 and 2020 at the Instructional Farm, KVK-Khowai, Tripura. TCG2 showed the highest average fruit weight (1.90 g), while TCG13 recorded the highest productivity (6.09 t/ha). TCG12 emerged as the second-best genotype for higher yield. In terms of pungency, TCG10 had the highest capsaicin content, while TCG10 and TCG3 recorded maximum ascorbic acid content. For rabi season cultivation in Tripura, TCG13 and TCG12 are recommended for higher yield, while TCG10 is the best suited for pungency. These findings can aid in commercializing local chilli genotypes for better utilization and market potential.Bangladesh J. Bot. 55(2): 321-327, 2026 (June)